Beyond Identification in Human Rights Culture: Voice of Witness's Voices from the Storm and Dave Eggers's Zeitoun. Issue 2 (17th February 2019) - Bex, Sean; Craps, Stef; Vermeulen, Pieter
ABSTRACT: In this article, we analyse two testimonial narratives written or published by Dave Eggers, an American author, editor, and publisher whose oeuvre shows a marked interest in harnessing the power of narrative to engage in human rights activism. Both narratives focus on the case of Abdulrahman Zeitoun, a Syrian-American who suffered in the aftermath of Hurricane Katrina and at the hands of the state through its response to that natural disaster. Our analysis challenges many of the assumptions with regard to affect that dominate the field of human rights and literature, which often takes for granted the intricate and treacherous process that undergirds a reader's engagement with testimonial narratives. Affective engagement with the reader is a key feature of Eggers's works, yet we show how it operates in a way that actively shapes the affective tenets of human rights culture in order to allow the reader to engage with the disempowered on more equal terms.